Normal range and risk factors for deviating body temperatures during the first 24 hours in term-born infants under standardised care: an observational study - Thomas Halvorsen; Trond Markestad; Lars Tveiten; Lien My Diep (BMJ Publishing Group, 2024)
Objective Body temperature for a known ambient temperature is not known for infants born at term. We aimed to determine the normal range and the incidences of hypothermia and hyperthermia during the first 24 hours of life in healthy term-born infants nursed according to WHO recommendations.Design Prospective observational study.Setting Norwegian single centre district hospital. Infants were observed during skin-to-skin care or when dressed in cots.Participants Convenience sample of 951 healthy infants born at term.Methods Delivery room temperature was aimed at 26-30°C and rooming-in temperature at 24°C. We measured rectal and room temperatures at 2, 4, 8, 16 and 24 hours of age.Main outcome measures Percentile curves for rectal temperature. Proportions and risk factors for hypothermia and hyperthermia.Results The mean (SD) room temperature was 24.0°C (1.1), 23.8°C (1.0), 23.8°C (1.0)., 23.7°C (0.9) and 23.8°C (0.9). The median (2.5, 97.5 percentile) rectal temperature was 36.9°C (35.7-37.9), 36.8°C (35.9-37.5), 36.9°C (36.1-37.5), 37.0°C (36.4-37.7) and 37.1°C (36.5-37.7). Hypothermia (<36.5°C) occurred in 28% of the infants, 82% of incidents during the first 8 hours. Risk factors for hypothermia were low birth weight (OR 3.1 (95% CI, 2.0 to 4.6), per kg), male sex, being born at night and nursed in a cot versus skin to skin. Hyperthermia (>37.5°C) occurred in 12% and most commonly in large infants after 8 hours of life. Risk factors for hyperthermia were high birth weight (OR 2.2 (95% CI, 1.4 to 3.5), per kg), being awake, nursed skin to skin and being born through heavily stained amniotic fluid.Conclusions Term-born infants were at risk of hypothermia during the first hours after birth even when nursed in an assumed adequate thermal environment and at risk of hyperthermia after 8 hours of age.